Implementación de una normativa en la ley de minería para regular las labores formalizadas de pequeños mineros en concesiones de minería a gran escala - Lozano Gualán, Segundo Intinahui (2014)
Mining since ancient times, has been a fundamental element in the development of human civilization, is currently stipulated in the Constitution of the Republic of Ecuador, as part of the Strategic Sectors. The lack of a clearly defined policy regarding mining in the country, has affected management problems of legal, fiscal, social and environmental order decades ago, that until now no solution. Despite the efforts made by this government in trying to design a schedule for Mining Artisanal Mining and Small-scale Mining, as stipulated in the Mining Act, a number of problems remain unsolved and configuring new ones. The great problem of Illegal Mining that takes place throughout the country, mostly in the category of small-scale mining, this type of activity carried out illegally and cause serious problems such as the destruction of nature, deforestation, pollution water, avoidance of tax liability as they do in a clandestine field not formulated a preliminary environmental study, so its removal from the place of activities is only destruction, unquantifiable environmental liabilities and other offenses stipulated. The work carried out small-scale mining and illegal anti technically have been and continue to be made even in spaces or areas free (state) and mining concessions granted to large Multinational Company; although it should be noted that the Agency Mining Regulation and Control (ARCOM), has met several operational level across the country, such as occurred on September 15, 2010 where 12 prosecutors, 1,500 police and 500 soldiers participated took and seized nine excavators, noting that the vast majority of machinery escaped hours before the operation, the other major operating was made in May 2011 that ended with the destruction of 70 excavators worth $ 15.2 billion this in the cantons of San Lorenzo and Eloy Alfaro in Esmeraldas province, plus there are often arrested for traffic fuels and explosives used for mining. It is known that illegal small-scale mining activity is carried out throughout the country, among other sectors we note the following: Conguime, Zapotillo Tiwintza, Morona, Chanaví, Paquisha, La Mana, etc. The appearance of the state in the past has delivered large concession areas almost complete majority Transnational Mining Company, apparently is the main focus for the town miners come stealthily illegitimate and mining activities, this flap the non-existence of a legal framework regulating the direct relationships between small miners and having Transnational Mining quality scale. A clear example is the existence of mining concessions on entire towns and cities, ancient indigenous populations grabbing areas such as in the case of the Multinational Mining Kinross Aurelian, which only has 16 concessions in Zamora Chinchipe thousands of acres in their favor and domain. To date there is no legal framework governing relations between frontal Small Miners and Mining large-scale framed as to achieve compliance with the law on legal, tax, social and environmental responsibility in the legal concept of Operation Contracts for small agreements mining, knowing that Art. 125 of the mining Act states that mineral rights are subject to assignment and transfer.